톡소포자충에 대하여 항톡소포자충효과가 있는 전승약물에 대한 연구 - 강경화(Jing Hua Jiang); 김화경(Hwa Kyoung Kim); 김춘매(Chun Mei Jin); 조향정(Hyang Jeong Jo); 김헌수(Hun Soo Kim); 윤기중(Ki Jung Yun); 박현(Hyun Park) (동의생리병리학회지, 2007)
The aim of this study was to confirm traditional medicine of ante-T. gondii effect. We searched 16 traditional medicines that have antiparisite effect from dongyibogam and Traditional Chinese Medicine. We have searched 3 medicines that was Quisqualis india L. var villosa Clark, Artemisia scoparia Waldstein and Loranthi Ramulus, Selectivity of these medicines was 2.9, 2.2 and 2.3, respectively, higher than spiramycin.